A Visitor’s Hybrid Smart Guide Control System - Mosiori, Cliff Orori (Engineering International, 2019)
Modern industrial society is filled with hybrid systems. The effectiveness of a control system is now a basic requirement in any institution. In general terms, hybrid systems are reactive systems that intermix discrete and continuous control components in which the discrete part of that control system makes the decision on behaving for the whole designed system and further decides if it can allow it to switch to another set of control protocols when appropriate conditions are availed. The continuous part only functions according to a specified protocol. Hybrid systems are common models used in digital (logic) and continuous networks and devices. Digital control programs detect, control, and supervise continuous and discrete systems using differential or difference equations. This principle was utilized in our design and reported thereof. Although this work developed a different method to deal with specific problems facing students at Technical University of Mombasa. An upgrade was recommended so as to extend the control system to the eye- impaired students and visitors. Since the issue of optimal smart control systems cannot be ignored in the design of new control systems with today’s requirements in our learning institutions, it was concluded that further research was necessary to bring about a fully reliable and well-developed control system able to use real-time and real routes as they exist at the university ground. This work reports a hybrid control guide system designed and implemented at the Technical University of Mombasa.